2019
DOI: 10.1186/s43042-019-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

MPL W515 L/K mutations in myeloproliferative neoplasms

Abstract: Background: Myeloproliferative neoplasms (MPNs) describe a group of diseases involving the bone marrow (BM). Classical MPNs are classified into chronic myelogenous leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). This classification is based on the presence of Philadelphia (Ph) chromosome (BCR/ABL1). CML is BCR/ABL1-positive while PV, ET, and PMF are negative. JAK2 p. Val617Phe pathological variant is the most associated mutation in BCR/ABL1-negative MPNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, our results showed that none of our MPN patients had MPL W515L/K mutations. Lieu and Eldeweny et al also reported that MPL W515L/K could not be found in 88 Taiwanese and 60 Egyptian patients with MPN [ 24 , 25 ]. Only 1–4% of MPL mutations were reported in two studies conducted among Korean and Chinese populations [ 20 ], [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that none of our MPN patients had MPL W515L/K mutations. Lieu and Eldeweny et al also reported that MPL W515L/K could not be found in 88 Taiwanese and 60 Egyptian patients with MPN [ 24 , 25 ]. Only 1–4% of MPL mutations were reported in two studies conducted among Korean and Chinese populations [ 20 ], [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis and bleeding are the most common complication that cause the morbidity and mortality of patients with myeloproliferative neoplasm 14,16,19,21,22,23,29,29,37,38,38,40,41 . This review showed that among a total of 14706 MPN patients, 2735 thrombotic events happened and there are also many bleeding recorded.…”
Section: Discussionmentioning
confidence: 99%